Investigations of the degree of asymmetry across the dayside magnetopause under southward interplanetary magnetic field using GEOTAIL observations - Koji Kondoh; Shin-ya Nitta (Earth, Planets and Space, 2024)
Abstract The magnetic reconnection environment around the dayside geomagnetopause under long-lasting southward interplanetary magnetic field (IMF) conditions is investigated using the in-situ observation by GEOTAIL satellite from 1994 to 2019. We focus on the degrees of asymmetry in the plasma density, ion temperature and the magnetic field strength between both sides of the magnetopause, that is, the ratio of the value in the magnetosphere to that in the magnetosheath in order to compute the much more realistic current sheet systems in numerical simulations. To exclude all of the interplanetary disturbance events such as Corotating Interaction Regions (CIRs) and Coronal Mass Ejections (CMEs), we investigate magnetopause crossings under long-lasting southward IMF conditions. GEOTAIL satellite sometimes repeatedly across the magnetopause during each pass due to the oscillating of the magnetopause. The degrees of asymmetry vary even during a single pass. This variation depends on the locus of the observation point, particularly the GSM Y-position, not on the time. The degrees of asymmetry in the plasma density, ion temperature and the magnetic field strength have significant variation in the data. The data points of the degree of asymmetry in the plasma density significantly spread in the duskside, while that in the magnetic field strength further widely spread in the dawnside. The degree of asymmetry in the plasma density and that in the magnetic field strength have fixed negative correlation on a log–log scale. Graphical Abstract